RANCANG BANGUN APLIKASI PERAMALAN HARGA EMAS DENGAN METODE PEMULUSAN EKSPONENSIAL WINTER - Lemantara, Julianto; sulistiowati, sulistiowati; Afwan, Moh (Fakultas Ekonomi Universitas PGRI Adi Buana, 2013)
The ability to know when to buy gold and to set gold selling price is important factor for gold merchants to achieve profit. However, it is difficult to determine the right time to buy gold because the gold price fluctuates quickly every time. As a result, many people and gold merchants are afraid that they would suffer from sales loss when the gold that they buy is more expensive than the one that they sell. Therefore, many gold merchants prefer to buy gold after selling out of their gold to avoid bigger loss. This research attempts to solve the problem by implementing system design for predicting gold price. This application predicts the gold price by taking minimum error value at MAPE and MSE calculation to achieve accurate prediction in determining the right time to buy and to sell gold in the future. The Winter's exponential smooting method can be applied to design an application for predicting gold price. The testing result shows that the error value between the actual data and prediction result is less that ten percent. It means that the prediction has a high accuracy.